Study of the crystallization of Fe78-xMoxSi9B13 amorphous alloys - Efthimiadis, KG; Chadjivasiliou, SC; Polychroniadis, EK; Ozer, M; Stergioudis, GA; Tsoukalas, IA (ELSEVIER SCIENCE BV, 1998)
The partial replacement of Fe atoms by Mo ones in amorphous Fe78Si9B13 alloys weakens their magnetic properties and shifts the crystallization process to higher temperatures. The crystallization is completed in three stages: During the first two, BCC Fe[Si,Mo] and BCT or orthorhombic [Fe,Mo](3)B phases are formed, respectively, the Mo content in these phases being less than 2 at%. The crystallization gets completed during the third stage, taking place at higher temperatures, where crystalline phases richer in Mo are formed. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: crystallization; amorphous alloys; magnetic materials; substitution effects; activation energy; Materials Science; Physics